Problems with Curriculum 2013 Implementation in Physical Health Education (PJOK) of Junior High School in Sub Rayon 05 Gunungjati District Cirebon Regency (Journal of Physical Education and Sports, 2019)
Curriculum 2013 is a new curriculum that has implemented in academic year of 2013/2014 and has carried out in Sub Rayon 05 Gunungjati District Cirebon Regency. The aim of this study is to know the problems with Curriculum 2013 implementation and its analysis in Physical Health Education (PJOK) in Sub Rayon 05 Gunungjati District Cirebon Regency. The type of this research is descriptive qualitative. The method used was survey and the technique of data collection used observation, interview, and documentation. The research population were all of Physical Health Education (PJOK) teachers and the headmaster. The research result showed that the problems of five state junior high schools located in Sub Rayon 05 are facilities and infrastructure from the five schools which are 20% good and 80% inadequate. Meanwhile, the implementation of school report book is 80% highlighted in assessment that is too complicated to be made for giving students score and 20% are said it is understandable. In Curriculum 2013, it is requires adequate facilities and infrastructure to support teaching and learning by using Curriculum 2013. In implementation stage, it needs to be improved in order to be more efficient and easy to fill school report book. The conclusion is generally the problem of Curriculum 2013 implementation in Physical Health Education in Sub Rayon 05 Gunungjati District Cirebon Regency, when the facilities and infrastructure is supportive, it will make teaching and learning process goes maximal and Curriculum 2013 assessment will be efficient and easy for teacher to fill school report book.